2021
DOI: 10.1186/s12888-021-03472-z
|View full text |Cite
|
Sign up to set email alerts
|

Mediating effects of self-stigma and depression on the association between autistic symptoms and recovery in patients with schizophrenia-spectrum disorders: a cross-sectional study

Abstract: Background Several studies have indicated that self-stigma is associated with depressive symptoms and could be a barrier to recovery in patients with schizophrenia-spectrum disorders. More recently, an association between autistic symptoms and self-stigma was found in schizophrenia-spectrum patients. This study aimed to investigate the association between self-stigma, autistic and depressive symptoms, and recovery in patients with schizophrenia. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…Scholars in Singapore have used a recovery scale based on recovery theory in a community setting and found that for individuals with schizophrenia, internalized stigma is negatively associated with personal recovery (Lim et al, 2020); that is, people who have a higher degree of self-stigma have worse personal recovery outcomes. A psychiatric survey from Japan showed consistent bivariate correlation analysis results for both adult inpatients and outpatients with schizophrenic spectrum disorders: self-stigma was strongly negatively correlated with recovery (Komatsu et al, 2021). Japanese scholars Komatsu et al (2021) also found, using a survey involving hospitalized and community-based patients with schizophrenia, that there was a moderate negative correlation between the degree of patients' self-stigma and the degree of recovery; that is, the higher the degree of self-stigma was, the lower the level of self-reported perceived recovery.…”
Section: Backg Rou N Dmentioning
confidence: 84%
See 2 more Smart Citations
“…Scholars in Singapore have used a recovery scale based on recovery theory in a community setting and found that for individuals with schizophrenia, internalized stigma is negatively associated with personal recovery (Lim et al, 2020); that is, people who have a higher degree of self-stigma have worse personal recovery outcomes. A psychiatric survey from Japan showed consistent bivariate correlation analysis results for both adult inpatients and outpatients with schizophrenic spectrum disorders: self-stigma was strongly negatively correlated with recovery (Komatsu et al, 2021). Japanese scholars Komatsu et al (2021) also found, using a survey involving hospitalized and community-based patients with schizophrenia, that there was a moderate negative correlation between the degree of patients' self-stigma and the degree of recovery; that is, the higher the degree of self-stigma was, the lower the level of self-reported perceived recovery.…”
Section: Backg Rou N Dmentioning
confidence: 84%
“…Scholars in Singapore have used a recovery scale based on recovery theory in a community setting and found that for individuals with schizophrenia, internalized stigma is negatively associated with personal recovery (Lim et al., 2020); that is, people who have a higher degree of self‐stigma have worse personal recovery outcomes. A psychiatric survey from Japan showed consistent bivariate correlation analysis results for both adult inpatients and outpatients with schizophrenic spectrum disorders: self‐stigma was strongly negatively correlated with recovery (Komatsu et al., 2021). Japanese scholars Komatsu et al.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Only one study assessed the relationship between autistic features measured with the PAUSS and internalized stigma, showing that more severe autistic symptoms are not correlated with worse internalized stigma, and could even have a protective effect on stigma resistance (59). On the contrary, the results of two studies conducted by another research group suggest that more severe autistic symptoms could be correlated to worse internalized stigma (87,88). However, in these studies the severity of autistic symptoms was not assessed through clinical observation or caregivers reports, but though self-rated assessment tools.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Self-stigma is associated with increased risks of social anxiety, hopelessness, psychiatric symptoms, and low treatment adherence among individuals with mental illnesses [ 7 , 13 , 14 ]. Both cross-sectional [ 15 , 16 ] and longitudinal [ 17 , 18 ] studies have revealed a significant correlation between self-stigma and depressive symptoms among individuals with schizophrenia. Although studies have examined the association between self-stigma and depression, few have focused on the association between self-stigma and suicide risk among individuals with schizophrenia.…”
Section: Introductionmentioning
confidence: 99%